Limitation clause of human rights in the 2013 Vietnamese constitution - Le, Quynh Mai (Đại học Quốc Gia Hà Nội, 2020)
The new Constitution of Vietnam was adopted by the National Assembly on 28 November 2013 and approved by 97.56% of the Assembly delegates. For the first time in the Constitution history, the term “human rights” was used before “Fundamental Rights and Duties of Citizens” in Chapter II (Chapter I: The political system). To underscore the importance, the value and the role of human rights and citizens’ rights, the Constitution and the State will consistently respect, protect and guarantee them. However, the state has the power to veshict all constitutional rights by law in imperative circumstances for the reasons of national defense, national security, social order and security, social morality and community well-being (Article 14.2 of the 2013 Constitution). The authors argue that the limitation on rights are as important as recognizing and assuring them, as virtually no right is absolute in light of the need to balance individual and community interests.This article is divided into two parts: the first part explores the achievements in recognizing human rights in the 2013 Constitution; the second part analyses the limitations of rights in Section 2, Article 14 of the Constitution of Vietnam and clarifies the correspondence between those limitations and the limitations in the International Human Rights Law. By doing so, this article will answer the question: what achievements have the 2013 Constitution recorded regarding recognizing and limiting rights to ensure compliance with international treaties?